Hva Er Et Adjektiv? Et Forsøk På En Prototypedefinisjon - Janik, Marta Olga (Folia Scandinavica Posnaniensia, 2013)
The article reviews various definitions of adjectival category in Norwegian, and shows that although they define it in different ways, the core of the definitions is always the same. However, there are some classes of adjectives, which are treated diversely by the Norwegian linguists because of the unlike set of criteria they use in their classifications. In my Ph.D. project, I analyze acquisition of Norwegian adjective agreement by Polish L1 speakers of L2 Norwegian. The aim of the present paper is to propose my own definition of adjective, which is based on prototypical and peripheral meanings. The definition shows a Norwegian prototype adjective (that is not unlike the adjectives presented by the Norwegian grammarians) and discusses the more peripheral cases. The definition focuses on the Norwegian adjectives, but also the Polish are mentioned.